How can growth be accelerated in Europe? - Matti Virén (Bank of Finland, 2012)
This paper deals with economic growth in Europe. The special emphasis is in key institutional factors that are commonly assumed to affect aggregate growth: functioning of labor markets, availability of labor and capital, and the size of government. For more explicit measures, we use the data on profit rates, average working hours, dependency ratios, tax rates and other measures of the size of government (e.g. employment shares), measures of price competitiveness, and finally the structure of production. The data also include the terms of trade, interest rates, and foreign demand as control variables. Empirical analysis makes use of cross-country panel data for EU15 countries for 1971-2010. The results suggest that profitability and competitiveness do indeed constitute the main determinants of growth. However, also other variables like working hours and the size of government appear to affect growth in an important manner. All in all, slowdown of growth in Europe does not appear to be a paradox but at least with some margin something can be done in achieving more ambitious growth rates.
URN:NBN:fi:bof-20140807351
Keywords: O40; O43; 330; growth; working hours; taxes; competitiveness